Air-side heat transfer characteristics of hydrophobic and super-hydrophobic fin surfaces in heat exchangers: A review. (May 2016) - Ganesan, P.; Vanaki, Sh.M.; Thoo, K.K.; Chin, W.M.
Abstract: A comprehensive literature review has been carried out to investigate the air-side heat transfer enhancement by different types of heat exchanger fin surfaces. In particular, the characteristics of hydrophobic and super-hydrophobic fin surfaces is compared with uncoated (bare) and hydrophilic fins. A summary of comparative findings under dry/wet conditions and frosting/defrosting conditions for heat exchanger and single plates is provided.